Shakespeare in our time : a Shakespeare Association of America collection - Callaghan, Dympna; Gossett, Suzanne (London ; Oxford ; New York ; New Delhi ; Sydney : Bloomsbury Arden Shakespeare, 2016)
'This volume marks the 400th anniversary of Shakespeare's death by reflecting on the unrivalled work of the Shakespeare Association of America and offering a unique collection of leading Shakespeare scholars outlining key developments in Shakespeare studies over the last two decades. These essays are complemented by younger scholars who respond and look forward to new fields of study and debate. As such the book offers a'state of the nation' look at Shakespeare criticism, covering all the key areas of research and study including gender, text, performance, the body, history, religion and biography. This is a must-read, comprehensive introduction to the key critical ideas surrounding Shakespeare's work and a stimulating exploration of where Shakespeare studies will go next.'--Publisher's website.
Machine generated contents note: Why Feminism Still Matters / Dympna Callaghan / Suzanne Gossett -- Just Imagine / Phyllis Rackin -- Letters, Characters, Roots / Kathryn Schwarz -- Deeds, Desire, Delight / Wendy Wall -- Rethinking Sexual Acts and Identities / Bruce R. Smith -- HexaSexuality / Mario DiGangi -- The Classroom / Madhavi Menon -- Money for Jam / David Bevington -- Extension Work / Marjorie Garber -- Facts, Theories, and Beliefs / Patricia Cahill -- What We Owe to Editors / Barbara A. Mowat -- What's Next in Editing Shakespeare / Lukas Erne -- Suicide as Profit or Loss / Sonia Massai -- Death and King Lear / Mary Beth Rose -- Shakespeare's Here / Michael Neill -- Spectatorship, Remediation, and One Hundred Years of Hamlet / Scott L. Newstok -- Performing Shakespeare through Social Media / James C. Bulman -- Reading Shakespeare through Media Archaeology / Pascale Aebischer -- Is Black so Base a Hue? / Alan Galey -- The Race of Shakespeare's Mind / Jean E. Howard -- Speaking of Race / Lara Bovilsky -- Shakespeare and the Bible / Ian Smith -- Shakespeare's Sources / Robert S. Miola -- Volver, or Coming Back / Ania Loomba -- Collaboration 2016 / Sarah Beckwith -- The Value of Stage Directions / Gary Taylor -- The Author Being Dead / Laurie Maguire -- Against Our Own Ignorance / Adam G. Hooks -- Circumnavigation, Shakespeare, and the Origins of Globalization / Susanne L. Wofford -- The Bard in Calcutta, India, 1835-2014 / Daniel Vitkus -- Bodies without Borders in Lear and Macbeth / Jyotsna G. Singh -- Potions, Passion, and Fairy Knowledge in A Midsummer Night's Dream / Gail Kern Paster -- Shakespeare and Variant Embodiment / Mary Floyd-Wilson -- Social Contexting / David Houston Wood --'Hic et ubique': Hamlet in Sync / Frances E. Dolan -- Playing in Context, Playing out Context / Bradin Cormack -- Historicizing Historicism / William N. West -- Minding Anachronism / William C. Carroll -- The Historicist as Gamer / Margreta de Grazia -- American Appropriation through the Centuries / Gina Bloom -- Appropriation 2.0 / Georgianna Ziegler -- Appropriation in Contemporary Fiction / Christy Desmet -- Shakespeare and Biography / Andrew Hartley -- Shakespeare's Friends and Family in the Archives / Peter Holland -- Biography vs. Novel / David Kathman -- The Classics as Popular Discourse / Lois Potter -- Shakespeare's Classicism, Redux / Coppelia Kahn -- Time, Verisimilitude, and the Counter-Classical Ovid / Lynn Enterline -- The Publicity of the Look / Heather James -- Public Women/Women of Valor / Paul Yachnin -- The Ghost of the Public University / Julia Reinhard Lupton -- William Shakespeare, Elizabethan Stylist / Henry S. Turner -- Nondramatic Style / Russ McDonald -- Shakespeare's Lexical Style / Stephen Guy-Bray -- Pluralizing Performance / Alysia Kolentsis -- The Study of Historical Performance / Diana E. Henderson -- Shakespeare/Performance / Tiffany Stern -- Shakespeare and Nature / W.B. Worthen -- Shakespeare without Nature / Rebecca Bushnell -- The Chicken and the Egg / Steve Mentz.
Keywords: Shakespeare, William, -- 1564-1616 -- Criticism and interpretation